Evulation Metal of Contamination by Natural Background and Average Earth's Crust Values in The Inci Stream Sediments Around Chromite Deposits in Guleman (Alacakaya-Elazığ), Turkey - Kalender, Leyla; Kara, Hatice (My University, 2023)
The total concentration of elements in the Inci stream sediments on the drainage network of chromite deposits was determined to evaluate the level of contamination by natural background, the average of ultramafic and mafic rocks in this study. The average concentration shows that toxic heavy metals originated from mineraliszing in the Inci stream sediments that have a controlling influence on accumulation and transportation both lithologically and anthropogenically. The metal enrichment factors of Pb, As, Ni, Sr, and Ba, and geoaccumulation factor values (Igeo) of Pb, As, Sr, Ba, and Rb indicated that these values are higher than background values and heavily contaminated. The highest metal concentrations and assessments of contaminants were obtained from ultramafic rock normalization. Enrichment factor (EF), contamination factor (CF), and Igeo values indicate that primary ore metals are represented by Pb, Cu, Mn, Ni, and Cr. Cr's enrichment factor (EF) is moderate contamination due to the high Cr concentration in the host rock. However, Cr is extremely contaminated according to the Earth's average in the stream sediments around the chromites deposit. The calculated Cu, Ni, and Cr threshold values are higher than the probable effect level (PEL) and threshold effect level (TEL). That is why these regions should be evaluated for relationships between human health and geochemistry in further multidisciplinary studies and considered important in terms of potential Cr, Cu, Mn, Ni, Pb and Zn mineralization.
Keywords: Contaminant factor; enrichment factor; geoaccumulation index; Guleman chromite deposite; Stream sediments